2010
DOI: 10.1128/aac.00210-10
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Daptomycin against Bacillus anthracis in a Murine Model of Anthrax Spore Inhalation

Abstract: Daptomycin demonstrated in vitro (MIC 90 , 4 g/ml) and in vivo activities against Bacillus anthracis. Twicedaily treatment with a dose of 50 mg/kg of body weight was begun 24 h after challenge and continued for 14 or 21 days; results were compared to those for controls treated with phosphate-buffered saline or ciprofloxacin. Day 43 survival rates were 6/10 mice for the 14-day and 9/10 mice for the 21-day treatment groups, compared to survival with ciprofloxacin: 8/10 and 9/10 mice, respectively. Culture result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Daptomycin efficacy has been demonstrated in models of hematogenous pneumonia induced by S. aureus (50,52) and pulmonary anthrax infections (53). The pathophysiology of these infections, both of which induce significant destruction of tissue integrity and consequent bacteremia, differs significantly from that of bronchio-alveolar pneumonia, which is largely confined to the intra-alveolar space (50).…”
Section: Daptomycin In Pneumonia Modelsmentioning
confidence: 99%
“…Daptomycin efficacy has been demonstrated in models of hematogenous pneumonia induced by S. aureus (50,52) and pulmonary anthrax infections (53). The pathophysiology of these infections, both of which induce significant destruction of tissue integrity and consequent bacteremia, differs significantly from that of bronchio-alveolar pneumonia, which is largely confined to the intra-alveolar space (50).…”
Section: Daptomycin In Pneumonia Modelsmentioning
confidence: 99%
“…In addition, it has been approved to treat S. aureus-induced bacteremia and infective endocarditis (21), and animal model studies suggest that it may be a useful alternative for treatment of inhalational anthrax (26). The mechanism of action involves the calcium-dependent insertion of DAP into the bacterial membrane, followed by depolarization of the membrane and extrusion of potassium ions, leading to arrest of macromolecular synthesis and to cell death (49,51).…”
Section: Daptomycin (Dap) Is a Cyclic Lipopeptide That Disrupts The Fmentioning
confidence: 99%
“…These results suggest that different bacteria, particularly those with significantly different membrane lipid profiles, likely evolve resistance by distinct pathways: PhG synthesis is perhaps not a relevant target in S. aureus because membranes in this organism are typically 80% PhG and significant reductions are not compatible with viability. Conversely, reductions in PhG synthesis could be a relevant pathway were DAP to be used clinically against Bacillus anthracis (26) or other bacteria with a similar membrane composition. A common feature of each of these resistance mechanisms is a reduction of the net negative charge of the cell membrane achieved by reductions in PhG levels in B. subtilis and increased LPG synthesis in S. aureus.…”
mentioning
confidence: 99%
“…Its unique mode of action [13] , ie, inserting into bacterial membrane and perturbing membrane function, makes it a useful alternate therapeutic for B anthracis infection if resistant isolates emerged. However, limited data are available on the www.nature.com/aps Xing YH et al Acta Pharmacologica Sinica npg effect of this drug on B anthracis species, and only one study has been reported by Heine et al [14] . This group demonstrated that daptomycin was active against B anthracis using a murine model of spore inhalation.…”
Section: Introductionmentioning
confidence: 99%